2013
DOI: 10.3892/ijmm.2013.1602
|View full text |Cite
|
Sign up to set email alerts
|

Positive feedback regulation between Akt phosphorylation and fatty acid synthase expression in osteosarcoma

Abstract: The activation of PI3K/Akt and the overexpression of fatty acid synthase (FASN) are frequently observed in human osteosarcoma (OS). In the present study, in order to investigate the possible association between the phosphorylation of Akt and FASN expression, immunohistochemical staining was conducted on 24 OS specimens from patients with pulmonary metastasis, which revealed a significant positive correlation between phosphorylated Akt (p-Akt) and the expression of FASN (R=0.469, P=0.04). To investigate the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Furthermore, the association between FASN downregulation and PI3K signaling, which is already documented (54–57) , could be confirmed by our data from respective genome-wide expression analyses ( Figure 4 ), which included the FASN inhibitor C75 as a control, thus emphasizing this pathway as a potential target for anticancer therapy (58) .…”
Section: Resultssupporting
confidence: 80%
“…Furthermore, the association between FASN downregulation and PI3K signaling, which is already documented (54–57) , could be confirmed by our data from respective genome-wide expression analyses ( Figure 4 ), which included the FASN inhibitor C75 as a control, thus emphasizing this pathway as a potential target for anticancer therapy (58) .…”
Section: Resultssupporting
confidence: 80%
“…Previous studies have shown that alteration of the PI3K/AKT pathway is strongly implicated in OS pathogenesis. Moreover, studies have suggested that inhibition of the PI3K/AKT pathway disrupts functions essential for OS progression (36,37). Graziano et al (38) found that Wilms' tumor gene 1 (WT1) silencing inhibits OS cell proliferation by downregulating PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…FASN modulates receptor localisation through palmitoylation and promotes the activation of oncogenic signalling pathways, such as the Akt/mTOR signalling pathway (5). The Akt/mTOR signalling pathway also promotes the transcription of FASN, thereby forming a positive feedback regulation (45,46). The downregulation of FASN inhibited cancer cell invasion and migration by targeting the Akt/mTOR signalling pathway (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%